The missionaries on the eastern frontier of the Cape Colony, 1799-1853 - Williams, D (My University, 1959)
This work attempts on the investigation into the activities of the missionaries of the Scottish (1), Wesleyan Methodist, and London Missionary Societies on the Eastern Frontier of the Cape Colony (2) during the years 1799-1853. The theme of the half-century is a triple failure: the failure to propagate Christianity among the amaXhosa, the failure to retain the goodwill of the colonists, and the failure to exercise significant political influence on the Cape administration. I have tried to explain why this occurred. There is a great need in South African historiography for detailed investigation into the contact between the missionaries and the Bantu. Missionary histories to date are of little value for an understanding of the problem of culture contact (J). With regard to the amaXhosa, there is no explanation, much less a frank admission, of the failure of the missionaries significantly to influence th4t race . Hitherto the tradition of missionary historiography has been to chronicle the increase of the number of mission institutions, and to accept this as evidence of the growth of Christianity as propagated by devoted and self-sacrificing missionaries. A re-assessment is long overdue. During and after the second half of the Nineteenth Century missionary circles were evaluating their achievements in Kaffirland, and were disappointed at the results. This missionary probe (4) has not been adequately reflected in contemporary South African missionary historiography. Of the missionary failure in Kaffirland, there is no doubt. Even today the amaXhosa is not a Christian nation. The publication of scurrilous attacks on missionaries in the form of pamphleteering literature (5) is symptomatic of the way in which such intellectual~ as are under the sway of Bantu Nationalism, is rejecting Christianity today (6). (Abbreviation abstract)
Submitted for the degree of Doctor of Philosophy in the the University of the Witwatersrand.
Keywords: Missions -- South Africa.; Missionaries -- South Africa.; South Africa -- Church history.